PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MELALUI MEDIA ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR KIMIA SISWA KELAS X PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Meronda, Devi Apriana; Haetami, Aceng; Tewa, Yuniati (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2021)
This study aims to find out students’ activity, students’ response and to compare students’ achievement who have participated in the problem based learning model (PBL) through the media of animation and student’ achievement who have participated in the direct learning model on the material of electrolyte and non-electrolyte solution. This study applied a quasi experimental design. The sample of this study consists of 35 students of class X MIA 2 (experimental class) and for the control class consists of 31 students of X MIA 1 who were taken by random sampling technique. The instruments were, observation sheet of students’ activity, the written test which consists of pre-test and post-test, and the questionnaire was filled by the students. The technique of data analysis was the t-test. The result of data analysis showed that there is a significant difference between students’ achievement who have participated in the problem based learning model (PBL) through the media of animation and student’ achievement who have participated in the direct learning model on the material of electrolyte and non-electrolyte solution. So, it can be concluded that the implementation of the problem based learning model (PBL) through the media of animation was not implemented successfully especially on the material of electrolyte and non-electrolyte solution.